Phanerozoic magma underplating and crustal growth beneath the North China Craton. (25th April 2017) - Ma, Qiang; Xu, Yi‐Gang; Zheng, Jian‐Ping; Sun, Min; Griffin, William L.; Xia, Xiaoping; Pan, Shao‐Kui
Abstract: Evidence for post‐Archaean crustal growth via magma underplating is largely based on U–Pb dating of zircons from granulite‐facies xenoliths. However, whether the young zircons from such xenoliths are genetically related to magma underplating or to anatexis remains controversial. The lower‐crustal xenoliths carried by igneous rocks in the Chifeng and Ningcheng (North China Craton) have low SiO2 and high MgO, indicating that parental melts of their protoliths were of unambiguous mantle origin. The xenoliths contain abundant magmatic zircons with late‐Palaeozoic ages, and have more radiogenic zircon Hf‐isotope compositions and hence younger model ages than ancient crustal magmas and the "reworking array" of the basement rocks. Our data suggest that the granulites represent episodic magmatic underplating to the lower crust of this craton in Phanerozoic time. Considering the observation that regional lowermost crust ( 5 km) is mafic and characterized by Phanerozoic zircons, this work reports an example of post‐Archaean crustal growth via magma underplating.